The inherent benefit of monetary unions - Dominik Groll; Tommaso Monacelli (Kiel Institute for the World Economy (IfW), 2016)
The desirability of flexible exchange rates is a central tenet in international macroeconomics. We show that, with forward-looking staggered pricing, this result crucially depends on the monetary authority's ability to commit. Under full commitment, flexible exchange rates generally dominate a monetary union (or fixed exchange rate) regime. Under discretion, this result is overturned: a monetary union dominates flexible exchange rates. By fixing the nominal exchange rate, a benevolent monetary authority finds it welfare improving to trade off flexibility in the adjustment of the terms of trade in order to improve on its ability to manage the private sector's expectations. Thus, inertia in the terms of trade (induced by a fixed exchange rate) is a cost under commitment, whereas it is a benefit under discretion, for it acts like a commitment device.
Keywords: E52; F33; F41; 330; monetary union; flexible exchange rates; commitment; discretion; welfare losses; nominal rigidities